1995
DOI: 10.1007/bf02212683
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-specific modulation of gastric mechanosensitivity in patients with functional dyspepsia

Abstract: Intraduodenal lipid infusion induces symptoms and increases sensitivity to gastric distension in patients with functional dyspepsia. To test whether these effects are specific for lipid, we compared the effects of intraduodenal infusions of either lipid or glucose on symptoms and gastric sensory and motor responses to gastric distension. Eighteen dyspeptic patients and nine controls were studied. The stomach was distended with a flaccid bag during isocaloric infusions (1 kcal/ml) of saline and either 10% Intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 17 publications
5
83
1
2
Order By: Relevance
“…As a consequence, acute capsaicin application evokes a feeling of warmth and pain, which can be desensitized during prolonged application. The finding that intraduodenal lipid (but not glucose) infusion sensitizes the stomach to distension in patients with functional dyspepsia, but not in controls 77 , suggests a cross-sensitization between mechanosensors and chemosensors and could explain why fatty meals can exaggerate symptoms related to gastric filling. Lipids in the duodenum can provoke symptoms through different possible mechanisms: direct neuronal stimulation, higher lipid sensitivity of enteroendocrine cells or nerves, increased levels of systemic or local cholecystokinin (which is secreted by lipid-activated enteroendocrine cells, stimulates the release of digestive enzymes and bile and induces satiety) and/or increased sensitivity to cholecystokinin involving type A cholecystokinin receptors 78 .…”
Section: Gastroduodenal Sensitivitymentioning
confidence: 94%
“…As a consequence, acute capsaicin application evokes a feeling of warmth and pain, which can be desensitized during prolonged application. The finding that intraduodenal lipid (but not glucose) infusion sensitizes the stomach to distension in patients with functional dyspepsia, but not in controls 77 , suggests a cross-sensitization between mechanosensors and chemosensors and could explain why fatty meals can exaggerate symptoms related to gastric filling. Lipids in the duodenum can provoke symptoms through different possible mechanisms: direct neuronal stimulation, higher lipid sensitivity of enteroendocrine cells or nerves, increased levels of systemic or local cholecystokinin (which is secreted by lipid-activated enteroendocrine cells, stimulates the release of digestive enzymes and bile and induces satiety) and/or increased sensitivity to cholecystokinin involving type A cholecystokinin receptors 78 .…”
Section: Gastroduodenal Sensitivitymentioning
confidence: 94%
“…These include delayed gastric emptying, hypersensitivity to gastric distension, impaired gastric accommodation to a meal, abnormal duodenojejunal motility, or central nervous system dysfunction (1)(2)(3)(4)(5)(6)(7). In addition, recent studies have suggested the importance of duodenal motor and sensory dysfunction in the genesis of dyspeptic symptoms (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Different factors such as delayed gastric emptying (Stanghellini V et al, 1996;Sarnelli G et al, 2003), hypersensitivity to gastric distension (Bradette M et al, 1991;Mearin F et al, 1991;Barbera R et al, 1995;Tack J et al, 2001), impaired gastric accommodation to a meal (Tach J et al, 1998), abnormal duodenojejunal motility (Holtmann G et al, 1996;Wilmer A et al, 1998), duodenal motor and sensory dysfunction Schwarz MP et al, 2001), duodenal hypersensitivity (Schwartz MP et al, 2001), Helicobacter pylori infection, and psychosocial factors have been implicated in the pathogenesis of FD. Among these factors, acid is thought to be more important because proton pump inhibitors (PPIs) and histamine 2 (H2)-receptor antagonists have been proposed to be effective therapies for a subset of patients with FD.…”
Section: Pathogenesis and Evaluationmentioning
confidence: 99%